A possible turning point for research governance in the life sciences - David R. Gillum (mSphere)
ABSTRACT On 5 May 2025, the White House issued Executive Order (EO) 14292, halting federally funded “dangerous gain-of-function” research and rescinding the 2024 Dual Use Research of Concern (DURC) and Pathogens with Enhanced Pandemic Potential (PEPP) policy. While intended to strengthen biosafety and biosecurity, the EO introduces vague definitions, an abrupt 120-day policy development deadline, and politically charged rhetoric that could undermine trust and buy-in. Researchers, biosafety professionals, and institutions are left with a biosecurity policy vacuum after this EO, which is creating uncertainty across the scientific enterprise. This perspective considers the EO’s implications through empirical findings and practitioner insight and argues for a tiered, adaptive risk governance model grounded in scientific rigor, operational clarity, and institutional expertise to navigate future biosecurity challenges.